Insights into the leaf cuticle fine structure of Ginkgoites skottsbergii Lundblad from the Albian of Patagonia and its relationship within Ginkgoaceae - Guignard, Gaëtan (2016)
New specimens of Ginkgoites skottsbergii Lundblad collected from the Albian Kachaike Formation at the type locality in Santa Cruz Province, Argentina are characterized with additional scanning and transmission electron microscopic observations and EDS elemental analysis. The micromorphology of the amphistomatic and 12-segmented leaf of G. skottsbergii shows a smooth lamina with straight and pitted anticlinal and slightly granulate periclinal walls, abundant epicuticular wax on the petiole surface, and monocyclic to partially dicyclic stomatal apparatuses with between six and eight papillate to non-papillate, finely striated subsidiary cells and guard cells with smooth walls. Palaeoenvironmental considerations suggest that G. skottsbergii was a mesophytic plant. The TEM studies of ordinary epidermal cell cuticles and subsidiary and guard cell cuticles reveal the general ultrastructural features of Ginkgoaceae. Using confidence intervals based on 30 statistical measurements and the Mann–Whitney test for five measurements of EDS ratios of the elements, 33 ultrastructural characters were identified that enabled discussion at different taxonomic levels. Comparisons with the previously studied Ginkgoites ticoensis Archangelsky reveal that 14 of these characteristics could be species features that reinforce the identity of G. skottsbergii, and 19 could be genus features. EDS analysis and comparisons with G. ticoensis yielded five ratios using Cl, N, K, S, and Ca, revealing seven ratios of potential species interest and eight ratios at the genus level among the three zones evaluated in the leaf cuticle of each species. A three-dimensional reconstruction of the cuticle and an ultrastructural identification key for each of the three types of cuticle are also provided, i.e., from the ordinary epidermal cell and the subsidiary and guard cells of the stomatal apparatus. Fruitful statistical comparisons with two previously studied ginkgos allow discussion of the relationships within the Ginkgoaceae with respect to 18 features, six of them being potentially significant at the genus level and four at the family level.